The urgent need for an Administrative Litigation Code in Ecuador - Villacreses-Valle, Jaime Andrés (2024)
This work exposes the origin of administrative litigation, the objective of its creation, principles that inform the process, highlight its specialty due to the issues that are known and resolved, review how effective judicial protection should be guaranteed, the tendency to abandon reviewing jurisdiction of the administrative act towards plenary and universal justice or protective justice and the regulation of administrative litigation in Ecuador and what should be considered for the promulgation of an Administrative Litigation Code.